Cadmium uptake and translocation in seedlings of near isogenic lines of durum wheat that differ in grain cadmium accumulation - Harris, Neil S (BioMed Central, 2004)
BACKGROUND: Cadmium (Cd) concentrations in durum wheat (Triticum turgidum L. var durum) grain grown in North American prairie soils often exceed proposed international trade standards. To understand the physiological processes responsible for elevated Cd accumulation in shoots and grain, Cd uptake and translocation were studied in seedlings of a pair of near-isogenic durum wheat lines, high and low for Cd accumulation in grain. RESULTS: In short-term studies (<3 h) using (109)Cd-labelled nutrient solutions, there were no differences between lines in time- or concentration-dependent (109)Cd accumulation by roots. In contrast, rates of (109)Cd translocation from roots to shoots following longer exposure (48–60 h) were 1.8-fold higher in the high Cd-accumulating line, despite equal whole-plant (109)Cd accumulation in the lines. Over the same period, the (109)Cd concentration in root-pressure xylem exudates was 1.7 to 1.9-fold higher in the high Cd-accumulating line. There were no differences between the lines in (65)Zn accumulation or partitioning that could account for the difference between lines in (109)Cd translocation. CONCLUSION: These results suggest that restricted root-to-shoot Cd translocation may limit Cd accumulation in durum wheat grain by directly controlling Cd translocation from roots during grain filling, or by controlling the size of shoot Cd pools that can be remobilised to the grain.